Poetic to popular, beauty and monstrosity in the Norwegian avant-garde theatre - Arntzen, Knut Ove (Amfiteater (Ljubljana), 2025)
In Norwegian theatre, the avant-garde may be less visible due to the very strong Ibsen tradition in stage directing marked by realism, which is the main tradition throughout Norwegian theatre history. However, there were attempts to create a Norwegian theatre avant-garde in the period between the 1920s and 1960s, which the author addresses in this article as a historical avant-garde perspective of beauty and monstrosity. The article focuses on the break from or cracking of the Ibsen tradition in stage directing, which indicates a break from traditional representational ways of playing Ibsen on stage, marked by the predominant realist stage directing and acting ideals, first during Ibsen’s own life and then during the decades after. The article also indicates the neo-avant-garde transition into the post-avant-garde from the 1960s to the 1980s and how Situationism came to influence it.
Keywords: beauty and monstrasity; folklora; folklore; gledališka režija; groteska; grotesque; historical avant-garde; lepota in monstruoznost; neoavantgarda; neo-avant-garde; norveška ibsenovska tradicija; Norwegian Ibsen tradition; postavantgarda; post-avant-garde; stage direction; zgodovinska avantgarda